Campbell Island Teal Anas aucklandica nesiotis bred in captivity - Preddey, Jeannie (Wildfowl, 1995)
One of the world's rarest ducks, the subantarctic Campbell Island Teal Anas aucklandica nesiotis, has bred for the first time in captivity. The successful captive breeding marks a major advance in the conservation of this teal. Captive breeding is an essential part of the recovery plan. The breeding behaviour of the captive teal was studied as part of a Masters thesis at Victoria University of Wellington, New Zealand.